Comparison of the diagnostic accuracy of whole-body MRI and whole-body CT in stage III/IV malignant melanoma - Hausmann, Daniel; Jochum, Susanne; Utikal, Jochen; Hoffmann, Richard Christoph Friedrich; Zechmann, Christian; Neff, Kurt Wolfgang; Goerdt, Sergij; Schönberg, Stefan; Dinter, Dietmar (Journal der Deutschen Dermatologischen Gesellschaft, 2011)
Background: Malignant melanoma (MM) is dramatically increasing in light-skinned populations worldwide. Staging and regular follow-up examinations are essential. The purpose of this study was to compare the diagnostic accuracy of whole-body MRI with the standard diagnostic algorithm (whole-body CT and brain MRI) in patients with stage III/IV MM. Patients and methods: A group of 50 consecutively admitted patients with stage III/IV MM were included in the study. Whole-body CT and brain MRI scans were performed. Additionally, all patients underwent a whole-body MRI (1.5 Tesla Magnetom Avanto, Siemens Healthcare Sector, Erlangen). The findings were compared on a lesion-by-lesion basis as part of clinical routine follow-up. Results: 33 patients received a follow-up CT and were evaluated. Overall, 824 lesions were detected. The sensitivity of whole-body MRI was observer-dependent. MRI was slightly less sensitive than CT according to the findings of the two most experienced observers (73.4 % vs. 78.2 %, p = 0.0744). CT was significantly more sensitive in the detection of small (1-5 mm) pulmonary nodules (2.9 % vs. 66.9 %, p < 0.0001). Yet overall, MRI was significantly more specific than CT (83.4 % vs. 50.4 %, p < 0.0001). Conclusions: Whole-body MRI in compliance with standard requirements for the observers (high level of experience) should be considered as an appropriate alternative to CT without ionizing radiation, particularly for young patients with advanced MM.